Fibronectin type III domain containing 5 expression in skeletal muscle in chronic heart failure—relevance of inflammatory cytokines. Issue 1 (31st March 2015) - Matsuo, Yae; Gleitsmann, Konstanze; Mangner, Norman; Werner, Sarah; Fischer, Tina; Bowen, T Scott; Kricke, Angela; Matsumoto, Yasuharu; Kurabayashi, Masahiko; Schuler, Gerhard; Linke, Axel; Adams, Volker
Abstract: Background: Chronic heart failure (CHF) is commonly associated with muscle atrophy and increased inflammation. Irisin, a myokine proteolytically processed by the fibronectin type III domain containing 5 (FNDC5) gene and suggested to be Peroxisome proliferator‐activated receptor gamma coactivator (PGC)‐1α activated, modulates the browning of adipocytes and is related to muscle mass. Therefore, we investigated whether skeletal muscle FNDC5 expression in CHF was reduced and if this was mediated by inflammatory cytokines and/or angiotensin II (Ang‐II). Methods: Skeletal muscle FNDC5 mRNA/protein and PGC‐1α mRNA expression (arbitrary units) were analysed in: (i) rats with ischemic cardiomyopathy; (ii) mice injected with tumour necrosis factor‐α (TNF‐α) (24 h); (iii) mice infused with Ang‐II (4 weeks); and (iv) C2C12 myotubes exposed to recombinant cytokines or Ang‐II. Circulating TNF‐α, Ang‐II, and irisin was measured by ELISA. Results: Ischemic cardiomyopathy reduced significantly FNDC5 protein (1.3 ± 0.2 vs. 0.5 ± 0.1) and PGC‐1α mRNA expression (8.2 ± 1.5 vs. 4.7 ± 0.7). In vivo TNF‐α and Ang‐II reduced FNDC5 protein expression by 28% and 45%, respectively. Incubation of myotubes with TNF‐α, interleukin‐1ß, or TNF‐α/interleukin‐1ß reduced FNDC5 protein expression by 47%, 37%, or 57%, respectively, whereas Ang‐II had no effect. PGC‐1α was linearly correlated to FNDC5 in all conditions. In CHF, animals circulating TNF‐α and Ang‐II were significantly increased, whereas irisin was significantly reduced. A negative correlation between circulating TNF‐α and irisin was evident. Conclusion: A reduced expression of skeletal muscle FNDC5 in ischemic cardiomyopathy is likely modulated by inflammatory cytokines and/or Ang‐II via the down‐regulation of PGC‐1α. This may act as a protective mechanism either by slowing the browning of adipocytes and preserving energy homeostasis or by regulating muscle atrophy.